Evaluating the Capability of Information Technology to Prevent Adverse Drug Events: A Computer Simulation Approach - Anderson, James G. (American Medical Informatics Association, 2002)
Background: The annual cost of morbidity and mortality due to medication errors in the U.S. has been estimated at $76.6 billion. Information technology implemented systematically has the potential to significantly reduce medication errors that result in adverse drug events (ADEs). Objective: To develop a computer simulation model that can be used to evaluate the effectiveness of information technology applications designed to detect and prevent medication errors that result in adverse drug effects. Methods: A computer simulation model was constructed representing the medication delivery system in a hospital. STELLA, a continuous simulation software package, was used to construct the model. Parameters of the model were estimated from a study of prescription errors on two hospital medical/surgical units and used in the baseline simulation. Five prevention strategies were simulated based on information obtained from the literature. Results: The model simulates the four stages of the medication delivery system: prescribing, transcribing, dispensing, and administering drugs. We simulated interventions that have been demonstrated in prior studies to decrease error rates. The results suggest that an integrated medication delivery system can save up to 1,226 days of excess hospitalization and $1.4 million in associated costs annually in a large hospital. The results of the analyses regarding the effects of the interventions on the additional hospital costs associated with ADEs are somewhat sensitive to the distribution of errors in the hospital, more sensitive to the costs of an ADE, and most sensitive to the proportion of medication errors resulting in ADEs. Conclusions: The results suggest that clinical information systems are potentially a cost-effective means of preventing ADEs in hospitals and demonstrate the importance of viewing medication errors from a systems perspective. Prevention efforts that focus on a single stage of the process had limited impact on the overall error rate. This study suggests that system-wide changes to the medication delivery system are required to drastically reduce mediation errors that may result in ADEs in a hospital setting.